1996
DOI: 10.1007/978-3-7091-6553-9_17
|View full text |Cite
|
Sign up to set email alerts
|

The gnotobiotic piglet as a model for studies of disease pathogenesis and immunity to human rotaviruses

Abstract: Summary. Gnotobiotic piglets serve as a useful animal model for studies of human rotavirus infections, including disease pathogenesis and immunity. An advantage of piglets ov~r laboratory animal models is their prolonged susceptibility to human rotavirus-induced disease, permitting cross-protection studies and an analysis of active immunity. Major advances in rotavirus research resulting from gnotobiotic piglet studies include: 1) the adaptation of the first human rotavirus to cell culture after passage and am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
110
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 116 publications
(113 citation statements)
references
References 18 publications
2
110
0
1
Order By: Relevance
“…The pair of virulent and attenuated Wa HRV strains provides a valuable tool to study the relationship between cytokine profiles, kinetics, and magnitude of responses and their relationships to the pathogenicity and immunity induced by these two rotavirus strains that differ in virulence (34,35). The pathogenicity of and immune responses to VirHRV and AttHRV have been well defined in gnotobiotic pigs (3,4,45,46,49,51).…”
Section: Discussionmentioning
confidence: 99%
“…The pair of virulent and attenuated Wa HRV strains provides a valuable tool to study the relationship between cytokine profiles, kinetics, and magnitude of responses and their relationships to the pathogenicity and immunity induced by these two rotavirus strains that differ in virulence (34,35). The pathogenicity of and immune responses to VirHRV and AttHRV have been well defined in gnotobiotic pigs (3,4,45,46,49,51).…”
Section: Discussionmentioning
confidence: 99%
“…These studies concluded that piglets are immunocompetent at birth [22], albeit with a largely 'immature' immune system that has not been previously in contact with antigens, resulting in a primary immune response, a less developed mucosal immune response and lower repertoire diversity than in adults [182]. Piglets also constitute a unique material for studying the development of the postnatal immune response [120] without any other antigenic stimulus, since they can be reared in germ-free [179,222] and antigen-free environments [108,129]. However, certain characteristics of the porcine lymphoid system may affect the immune system, and thus require the development of appropriate cellular and molecular reagents and tools [184].…”
Section: Introductionmentioning
confidence: 99%
“…Pigs are monogastrics and leverage the gastrointestinal, nutritional, metabolic and immunologic similarities of humans. [91][92][93] neonatal and weaned C57bl/6 mouse model with or without malnutrition. Another neonatal model was developed more recently using six-day-old C57BL/6 mice to study EAEC induced infantile diarrhea.…”
mentioning
confidence: 99%